Thermal enhancement of triangular fins based on spanwise distance of vortex generators - Akcayoglu, Azize; Nazli, Celal (SAGE Publications, 2016)
In this study, the influence of spanwise positions of vortex generators on the fin performance is determined numerically by considering global and local flow and heat transfer fields. The vortex generators are located on the inclined surfaces of equilateral triangular fins and the spanwise distances between them are altered as much as possible depending on the extents of the triangular duct. “RNG k-ɛ” turbulence model with “Enhanced wall treatment” option is determined as the best turbulence model to predict the flow fields inside the triangular fins with built-in vortex generators, for Reynolds number of 5000. It is found that the best performance is achieved when the spanwise distance between the common flow up and common flow down type vortex generator pairs and the triangular duct base are equal to 0.23 and 1.11 times the vortex generator length, respectively. The optimum spanwise distance between the vortex generators is determined as 0.88 times the vortex generator length. The determined values reinforced the secondary flow interactions including mixing of hot and cold fluids, generation of turbulence, swirling motion of vortices, and interaction of vortices with the main flow. The obtained results are useful in designing triangular heat exchangers with built-in delta-winglet type vortex generators.